Chronic severe asthma in adults. (May 2016) - Bayes, Hannah K.; Thomson, Neil C.
Abstract: Patients with chronic severe asthma remain symptomatic despite intensive treatment with high-dose inhaled corticosteroids and long-acting β2 -adrenoreceptor agonists; they therefore frequently require systemic corticosteroids. These patients experience substantial morbidity, reduced life expectancy and high use of healthcare resources. Patients should be assessed for treatment adherence, potential asthma triggers, coexisting or alternative diagnoses and undertreatment. A stepwise pharmacological treatment approach should be combined with facilitation of adherence and inhaler technique, non-pharmacological treatments where appropriate and supported self-management. Specialist asthma services may start additional treatments (e.g. monoclonal antibody therapy, bronchial thermoplasty) in patients with persistent poorly controlled asthma.